Uma experiência de formação continuada: o papel do coordenador pedagógico e do registro reflexivo na formação de professores de Educação Infantil - Bartholomeu, Fabiana (2016)
This research aimed to investigate the role that the pedagogical coordinator exerts on the building process of reflective records, as it is used like a continuing education approach in the course of work, for children education teachers placed in an indirect kindergarten from the municipal system of the city of São Paulo, also considering it’s possible contribution to the teacher’s professional development. This study is a qualitative research and used as a methodological procedure the documental analysis of records registered by the teachers during the period from 2014 to 2016. The records explored four analysis classes: the focus on the child and the reflective writing training; the relation between practice and theory; the awareness and the intent; and, the manifestation of emotions during the writing. The authors used as the theoretical support were: Dewey (1959), Schön (1983), Nóvoa (1992), to discuss about the reflective teacher and the importance of the reflective practices; and Clementi (2012), Schön (1992), Nóvoa (1992), Placco (1994), Freire (1996), Warschauer (1993, 2001) e Zabalza (2004), to explore the role of the pedagogical coordinator. It was verified that, when registering in a reflective way, the teacher recognizes herself as a knowledge mobilizing and socializing, in other words, to the other and to the context, resulting in new learning and wisdom. It was also verified that, when the observations and records from the pedagogical acting were shared to each other, it made possible to build practical and theoretical reflections to be awareness of this acting, boosting changes in/of the teaching act. The results highlight the importance of the reflective records and the skills that it provides, and in addition show that the critical reflective practice may be considered as a booster for changes in the teaching quality of children education